Evaluation of three methods for preservation of Azotobacter chroococcum and Azotobacter vinelandii - Rojas Tapias, Daniel (2013)
Because the use of bacteria for biotechnological processes requires maintaining their viability and genetic stability, preserving them becomes essential. Here, we evaluated three preservation methods for A. chroococcum C26 and A. vinelandii C27; preservation methods: cryopreservation and immobilization in dry polymers for 60 days, and freeze-drying for 30. We evaluated their efficiency by counting viable cells and measuring nitrogen fixation activity. Additionally, we assessed the effect of three protective agents for freeze-drying, three for cryopreservation, and four polymers. Freeze-drying proved the best technique to maintain viability and activity, followed by immobilization and cryopreservation. Bacterial nitrogen fixing ability remained unchanged using the freeze-drying method, and bacterial survival exceeded 80%; S/BSA was the best protective agent. Immobilization maintained bacterial survival over 80%, but nitrogen fixation was decreased by 20%. Lastly, cryopreservation resulted in a dramatic loss of viability for C26 (BSR approx. 70%), whereas C27 was well preserved. Nitrogen fixation for both strains decreased regardless of the cryoprotective agent used (P < 0.05). In conclusion, the success of Azotobacter preservation methods depend on the technique, the protective agent, and the strain used. Our results also indicated that freeze- drying using S/BSA is the best technique to preserve bacteria of this genus.